Profesionalni razvoj ravnateljev in vodenje šole - Ivanuš-Grmek, Milena (Šolsko polje, 2007)
The first part of this article is about the importance of headmaster's professional development for school leadership. For a school development it is essential rule of a headmaster who influences other teachers. In the second part of the article experiences with professional biography in leadership teaching and professional development of headmasters are shown. In the article are presented two important expects of headmaster's work - a collaboration with social environment and a preparation of school work.
Keywords: kvaliteta; profesionalni razvoj; ravnateljevanje; ravnatelji; vodenje; vzgoja in izobraževanje